2015
DOI: 10.1111/gbb.12240
|View full text |Cite
|
Sign up to set email alerts
|

Recognition deficits in mice carrying mutations of genes encoding BLOC‐1 subunits pallidin or dysbindin

Abstract: Numerous studies have implicated DTNBP1, the gene encoding dystrobrevin-binding protein or dysbindin, as a candidate risk gene for schizophrenia, though this relationship remains somewhat controversial. Variation in dysbindin, and its location on chromosome 6p, has been associated with cognitive processes, including those relying on a complex system of glutamatergic and dopaminergic interactions. Dysbindin is one of the seven protein subunits that comprise the biogenesis of lysosome-related organelles complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…This set of behavioral and cognitive phenotypes differentiates the spp mice from the widely used sdy mice and offers a novel model of dysbindin alterations that may be used to study specific recognition memory deficits. Our results corroborate recent findings of recognition deficits in dysbindin and pallidin deletion mouse models that further highlight a potential link between dysbindin alterations and recognition processes. Pallidin is a related biogenesis of lysosome‐related organelles complex 1 (BLOC‐1) protein that is expressed in the brain and may interact with dysbindin to produce phenotypic variation .…”
Section: Discussionsupporting
confidence: 91%
“…This set of behavioral and cognitive phenotypes differentiates the spp mice from the widely used sdy mice and offers a novel model of dysbindin alterations that may be used to study specific recognition memory deficits. Our results corroborate recent findings of recognition deficits in dysbindin and pallidin deletion mouse models that further highlight a potential link between dysbindin alterations and recognition processes. Pallidin is a related biogenesis of lysosome‐related organelles complex 1 (BLOC‐1) protein that is expressed in the brain and may interact with dysbindin to produce phenotypic variation .…”
Section: Discussionsupporting
confidence: 91%
“…For example, the absence of platelet delta granules is currently essential for the HPS diagnosis, but a subset of subjects with BLOC‐1 may have normal/decreased platelet delta granules and may therefore not be considered for an HPS diagnosis. In addition, reported brain‐associated functions of BLOC‐1 (A. Ito et al, 2018; Newell‐Litwa et al, 2010; Spiegel, Chiu, James, Jentsch, & Karlsgodt, 2015) may underlay a neurologic phenotype of BLOC‐1 deficiency. Recognition of these features may facilitate the diagnosis of affected individuals with HPS subtypes associated with BLOC‐1 defects.…”
Section: Introductionmentioning
confidence: 99%
“…Following reports of a possible association between common variants in the human dysbindin-encoding gene and schizophrenia 1518 , a number of studies have found behavioural and electrophysiological abnormalities in the sandy mice (reviewed in refs 5 and 6), with a subset of these behavioural abnormalities recently reported for pallid mice as well 19 . In addition, pallid mice showed enhanced physiological and behavioural responses to morphine administration compared to the wild-type (WT) C57BL/6J strain.…”
Section: Introductionmentioning
confidence: 99%